1988
DOI: 10.1007/bf00394873
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of nitrate by bacteroids of Bradyrhizobium japonicum in the soybean root nodule

Abstract: Bacteroids of Bradyrhizobium japonicum strain CB1809, unlike CC705, do not have a high level of constitutive nitrate reductase (NR; EC 1.7.99.4) in the soybean (Glycine max. Merr.) nodule. Ex planta both strains have a high activity of NR when cultured on 5 mM nitrate at 2% O2 (v/v). Nitrite reductase (NiR) was active in cultured cells of bradyrhizobia, but activity with succinate as electron donor was not detected in freshly-isolated bacteroids. A low activity was measured with reduced methyl viologen. When b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
4

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 35 publications
4
21
0
4
Order By: Relevance
“…Also, values of Oi measured at TNAPeak were lower than those measured previously in minimally disturbed soybean nodules (King and Layzell, 1991). However, the TNA, k values were equal to, or greater than, most TNA values reported in the literature for nodulated roots of soybeans (5.1-54 kmol g-' dry weight of nodule h-') (Ralston and Imsande, 1982;van Kessel and Bums, 1983;van Berkum et al, 1985;Bethlenfalvay et al, 1987;Giannakis et al, 1988;Imsande, 1988;Kanayama et al, 1990;Kohl et al, 1991). This observation is consistent with the suggestion that many of the standard methods that have been used for assay of nitrogenase activity inhibit the process being measured (Minchin et al, 1983(Minchin et al, , 1986, presumably due to a reduction in Oi and the rate of nitrogenase-linked respiration.…”
Section: Extemal Poz (%)mentioning
confidence: 63%
“…Also, values of Oi measured at TNAPeak were lower than those measured previously in minimally disturbed soybean nodules (King and Layzell, 1991). However, the TNA, k values were equal to, or greater than, most TNA values reported in the literature for nodulated roots of soybeans (5.1-54 kmol g-' dry weight of nodule h-') (Ralston and Imsande, 1982;van Kessel and Bums, 1983;van Berkum et al, 1985;Bethlenfalvay et al, 1987;Giannakis et al, 1988;Imsande, 1988;Kanayama et al, 1990;Kohl et al, 1991). This observation is consistent with the suggestion that many of the standard methods that have been used for assay of nitrogenase activity inhibit the process being measured (Minchin et al, 1983(Minchin et al, , 1986, presumably due to a reduction in Oi and the rate of nitrogenase-linked respiration.…”
Section: Extemal Poz (%)mentioning
confidence: 63%
“…Smith and Smith (1986) produced evidence that NOa-reaches the infected region of nodules, and that it is reduced to N20 by bacteroid enzymes. On the other hand Sprent et al (1987) suggested that NOa-could not penetrate into the infected region, and Giannakis et al (1988) concluded that NO2-accumulation in soybean nodules is an artifact resulting from the mixing of infected and cortical regions. Becana et al (1989) attributed these discrepancies to the differences in the experimental conditions used in terms of NO3-concentration, treatment duration, or plant-microbe species.…”
Section: Discussionmentioning
confidence: 97%
“…Kanayama and Yamamoto proposed that NO formed from NO 3 -binds to Lb to make nitrosylleghemoglobin and defect the O 2 binding activity (Kanayama & Yamamoto, 1990). On the other hand, Giannakis et al (1988) suggested that nitrate metabolism does not occur in symbiotic region of soybean nodule, even when a dissimilatory NR is expressed, because of restricted access of nitrate. Leghemoglobin (Lb) plays a crucial role in N 2 fixation of leguminous nodules by facilitating O 2 supply to the bacteroids.…”
Section: Nitrate Inhibition Of Nodule Growth and Nitrogen Fixationmentioning
confidence: 99%